Boron Isotope Separation Using Chemical Isotope Exchange with Thermal Flow Reversal; Russian Physics Journal; Vol. 67, iss. 6 - Sukhar Р. А. Pavel Andreevich (Elementary particle physics and field theory, 2024)
Title screen